PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATERI IPAS DI SD NEGERI 43 PALEMBANG - Nisa Hikmatunazilah; Jayanti; Diana Widhi Rachmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem-Based Learning model on the learning outcomes of fourth-grade elementary school students in science. This research was motivated by the low learning outcomes of fourth-grade students in science at State Elementary School 43 Palembang. This study used a quantitative research method using the Tru Experimental Design method. The design used a Posttest-Only Control Group Design. The population of this study was fourth-grade students at State Elementary School 43 Palembang. The sample size was 24 students in class IV.A and 22 students in class IV.B. Data collection techniques used documentation and tests. The results showed that the average score obtained by the researchers from the posttest questions for the experimental class was 84.71667, while the control class was 63.125. Based on the analysis using the Independent Sample T-Test, with the criterion Hα being accepted if t count > t table, with the obtained data t count = 5.359 and t table = 2.015 with a significance level of 0.05, Hα is accepted. Based on the results of the study, it can be concluded that the Problem-Based Learning model has a significant influence on the learning outcomes of the science material at SD Negeri 43 Palembang